The Effectiveness Of Coaching And Counseling Strategies In Improving Nurses' Attitudes In Communication, Teamwork And Stress Management At RSUD M. Natsir Solok - Febrian Rahmat Suwandi SN; Masyitah Fadhani; Nurul Rusma (Universitas Pahlawan Tuanku Tambusai, 2026)
Background: Maintaining quality of care and patient safety is the responsibility of healthcare workers, and nurses play a crucial role in this regard. This role extends beyond cognitive and technical skills; interpersonal skills are essential for delivering excellent healthcare. These interpersonal skills include effective communication, teamwork, and stress management. Purpose: To determine The effectiveness of coaching and counseling strategies in improving nurses' attitudes in communication, teamwork and stress management at RSUD M. Natsir Solok Methods: This research will be conducted for 1 year, the research method used is quantitative with a quasi-experimental design with a pre- and post-test design without a control group which aims to test the influence of leadership coaching and counseling strategies by measuring nurses' attitudes in communication, teamwork and stress management before (pre-test) and after (post-test). The intervention in this research is to provide coaching and counseling on communication, teamwork and stress management.. Results: Nilai P Value = 0.001 < 0.005 dapat diartikan bahwa terdapat pengaruh Coahing dan Couseling Stategi terhadap peningkatan Sikap dalam Komunikasi, Kerjasama Tim dan Manajemen Stres. Dengan Masing-masing nilai Selisih Mean +2.5, + 2.0 dan + 2.0. Conclusion: Practically, the results of this study can provide implications for hospital management, particularly in the nursing field, to develop the potential of nursing human resources with a focus on improving interpersonal skills through the implementation of coaching and counseling strategies. Ultimately, nurses can contribute significantly to improving the quality of nursing services in hospitals Keywords: Leadership Coaching; Counseling; Nurse Attitudes; Teamwork; Stress Management.